ANALISIS PROSEDUR PEMBERIAN KREDIT PADA PT PERMODALAN NASIONAL MADANI (PNM) ULAMM (UNIT LAYANAN MODAL MIKRO) PULO BRAYAN MEDAN - Sunarto, Hawa Aplinda; Asmalidar (Jurnal Budgeting, 2023)
This final report is about "Analysis of Credit Provisioning Procedures at PT Permodalalan Nasional Madani (PNM) ULaMM (Unit Layanan Modal Mikro) Pulo Brayan Medan. The purpose of this study was to determine the procedure for granting credit at PT Permodalan Nasional Madani (PNM) ULaMM (Unit Layanan Modal Mikro) Pulo Brayan Medan. Methods of data collection by interviews, observation and literature study. Then the data is compared with the existing theory. The results of this study indicate that the procedure for granting credit at PT Permodalan Nasional Madani (PNM) Micro Capital Service Unit (ULaMM) Pulo Brayan Medan consists of 15 stages, namely submission of documents, investigation of loan documents, 1st interview, on the spot, track checking, bi checking, taking photos of activities and place of business, place of guarantee and customer's residence, entering the results of interviews with customers into proposals, reviewing with committees, 2nd interview, 3rd interview, credit decision, signing of credit agreement, realization of credit, and channeling or withdrawing funds, while the procedure for extending credit according to theory only consists of 9 stages.